IMPLEMENTASI BUDAYA SEKOLAH BERWAWASAN LINGKUNGAN DALAM MEMBENTUK KARAKTER PEDULI LINGKUNGAN SISWA SEKOLAH DASAR - Ummi Nur Rokhmah; Misbahul Munir (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2021)
The purpose of this study is describe implementation of environmental school culture for shaping character environmental care students at SDN Temas 01 Batu. This study used a qualitative approach with descriptive research. The study is conducted in SDN Temas 01 Batu with the subject of his research is the principal, 3 teachers, 4 students, 1 janitor, 1 cafeteria guard and 2 parents of students. Data is collected through interview, observation, and documentation. Data analysis is carried out through 3 stages, datareduction, data display and verification. The validity of the information is tested by triangulation of techniques and triangulation of sources. The research results show that environmental school culture is implemented through 3 steps, planning, implementation and evaluation. Planning activities are forming school environmental management team, making environmental studies and planning environmental actions. Activities carried out during implementation are make environmental policies, implement environmental based curricula, conduct participatory based environmental activities, and manage environmental supporting facilities. The success of the implementation is evaluated by monitoring the state of biodiversity in schools, electricity bills and spending on purchasing office stationery, weighing the amount of waste and monitoring students' ability to manage the environment in terms of cognitive, affective and psychomotor aspects. The supporting factor that influences the implementation of an environmental school culture is the location of the school which is in a location that is still beautiful and gets a lot of support from outside parties. While the inhibiting factor is limitation of budget, there are still students who lack awareness in sorting waste and there is still a lot of plastic waste in schools.